ISSUES OF USING ARTIFICIAL INTELLIGENCE IN THE APPLICATION OF LOGISTICS IN ENTREPRENEURIAL ACTIVITY - Karrieva Yakutxon Karimovna (Modern American Journals, 2026)
The rapid development of digital technologies has significantly transformed modern entrepreneurial activity, particularly in the field of logistics management. Artificial Intelligence (AI) plays a crucial role in optimizing supply chains, improving demand forecasting, enhancing transportation efficiency, and reducing operational costs. The integration of AI-driven systems enables businesses to automate decision-making processes, analyze large volumes of real-time data, and increase overall competitiveness.The purpose of this study is to examine the key issues related to the application of Artificial Intelligence in logistics within entrepreneurial activity. The paper analyzes current AI-based tools such as machine learning algorithms, predictive analytics, intelligent routing systems, warehouse automation, and robotics. Particular attention is given to implementation challenges, including high investment costs, data security concerns, lack of qualified specialists, and integration with existing enterprise resource planning systems.The findings suggest that effective implementation of AI technologies in logistics can significantly enhance operational performance, reduce human error, and improve customer satisfaction. However, successful adoption requires strategic planning, digital infrastructure development, and regulatory support.
Keywords: Artificial Intelligence; logistics management; entrepreneurship; supply chain optimization; digital transformation; predictive analytics; intelligent transportation systems; automation; business efficiency; innovation